The First Evangelical Indian Congress - Winter, Ralph D. (Practical anthropology, 1962)
The “First Evangelical Indian Congress” took place the last weekend of October 1961 in a Tarascan village on the shores of Lake Pátzcuaro, Michoacán, Mexico. Here were gathered persons from some thirteen Indian groups of Mexico and one from Guatemala, upon invitation of the Tarascan evangelical congregations, for two days of fellowship and discussion of common problems. The present article is condensed from a report by Ralph D. Winter, who participated as an observer and who writes his impressions of some of the values of this type of inter-Indian Christian participation and their bearing upon the problems of relating the Indian work to the national churches which represent the dominant culture. This is followed by an article by Dow F. Robinson, which presents an interpretation of some of the conclusions that were reached by one of the groups, in terms of their cultural setting.